Robust finite-time anti-swing control for quadrotor slung-load system based on compensation function observer - Xiaoning Yu; Liaozhang Li; Kun Yan; Jiayong Fang; Peng Zhang; Bo Cheng (PLoS ONE, 2026)
In this work, a robust finite-time anti-swing controller is proposed for the quadrotor slung-load system subject to external disturbances. To stabilize the swing angles of the payload, an energy function incorporating both kinetic energy and potential energy is constructed such that the swing angles gradually converge to zero. Since the swing angle information is integrated into the energy function, the global convergence of the quadrotor slung-load system is improved. Meanwhile, a novel compensation function observer is designed to suppress unknown disturbances, thereby enhancing the robustness of the closed-loop system. Compared with the traditional extended state observer method, the developed compensation function observer achieves a faster convergence rate and higher observation accuracy with a smaller observer gain. To further improve the fast convergence performance of the entire closed-loop system, the finite-time control technique is adopted to design the robust anti-swing flight control scheme based on the Lyapunov stability theory and backstepping approach. This control scheme guarantees that all error signals of the quadrotor slung-load system are uniformly ultimately bounded. Finally, simulation verification is performed and comparison results are provided to illustrate the superior effectiveness of the presented control algorithm.